A method for preparing methacrylic acid
By using a catalyst with a three-functional catalyst of hydrolysis-analyzed dehydrogenation-condensation catalyst in a fixed bed reactor, the problems of high raw material cost and low catalyst activity in the existing methacrylic acid synthesis method are solved, and the efficient preparation of methacrylic acid and The effect of co-generation of hydrogen.
Patent Information
- Application Number
- CN202111479258.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-06
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2041-12-06
AI Technical Summary
In the existing methacrylic acid synthesis methods, the raw material cost is high, the equipment is complex, the selectivity is low, and the catalyst activity is generally low, making it difficult to effectively prepare methacrylic acid.
Using a fixed bed reactor, a catalyst with three functions of hydrolysis-analysis-absorbent dehydrogenation-condensation is used to generate methacrylic acid through the hydrolysis-dehydrogenation-condensation reaction of methyl propionate and water. At the same time, hydrogen is produced, and the catalyst is natural. Or artificial weak acidic materials, metal oxides and heteropolyacids, optimize reaction conditions to improve yield and selectivity.
The cheap and easy-to-access catalyst design is achieved, which improves the yield and selectivity of methacrylic acid, up to 73%, and produces hydrogen in parallel, simplifies the reaction process and reduces production costs.
Smart Images

Figure BDA0003394784940000021 
Figure BDA0003394784940000191 
Figure BDA0003394784940000201
Abstract
Description
Technical Field
[0001] The invention relates to a method for synthesizing methacrylic acid, in particular to a method for preparing methacrylic acid by catalysis of methyl propionate and H2O and co-producing hydrogen. Background Art
[0002] Methacrylic acid is an important organic chemical raw material and polymer intermediate, mainly used in organic synthesis and polymer preparation. It can be used as a raw material for organic reagents and synthetic rubber. It is used to manufacture thermosetting coatings, synthetic rubber, fabric treatment agents, insulating materials, adhesives and ion exchange resins. It is a monomer for manufacturing acrylic ester solvent-based and emulsion-based adhesives to improve the bonding strength and stability of adhesives.
[0003] The most important derivative of methacrylic acid is methyl methacrylate. Methyl methacrylate is the monomer of polymethyl methacrylate and the raw material for producing organic glass. It can be used for windows of aircraft and civil buildings, and can also be processed into buttons, sun filters and car lamp lenses, etc. The coating produced has excellent suspension, rheological and durability properties; the adhesive made can be used for bonding metal, leather, plastic and building materials; methacrylate polymer emulsion is used as a fabric finishing agent and antistatic agent. It can also be copolymerized with other vinyl monomers to obtain products with different properties. It is used to make lubricant additives, plastics, adhesives, resins, wood impregnation agents, motor coil impregnation agents, ion exchange resins, paper polishes, textile printing and dyeing auxiliaries, leather treatment agents and insulation potting materials, etc.
[0004] The acetone cyanohydrin process is commonly used in the United States, Western Europe and other countries to produce methacrylic acid. The raw material acetone of the acetone cyanohydrin process comes from the oxidation of cumene and grain fermentation, and hydrocyanic acid comes from the byproduct of acrylonitrile and the catalytic ammoxidation process. The raw material of the acetone cyanohydrin process is highly toxic HCN. The production cost is high when it is used as the main product (low-cost HCN can be obtained as a byproduct of acrylonitrile production, but the safety of transportation cannot be guaranteed). At the same time, a large amount of sulfuric acid is used, which not only pollutes the environment, but also causes equipment corrosion. Therefore, various countries have developed some other methods, including: isobutylene (tert-butyl alcohol) oxidation method, isobutane oxidation method, ethylene carbonylation method and propylene carbonylation method. Among them, the isobutylene (tert-butyl alcohol) oxidation method has the greatest impact at present.
[0005] Asian companies such as Japan's Kyodo Monomer mainly use the isobutylene method, which is used for smaller-scale plants and is economically competitive. Isobutylene usually comes from the residual C4 fraction after cracking C4 and extracting butadiene. Isobutylene is converted into tert-butyl alcohol by hydration, so that isobutylene and n-butylene can be separated. In addition, tert-butyl alcohol also comes from the co-product of propylene and isobutane co-oxidation to produce propylene oxide. China has abundant C4 resources, and Qilu Petrochemical has direct oxidation technology for isobutylene.
[0006] The isobutylene oxidation method first oxidizes isobutylene into methacrolein, then oxidizes it into methacrylic acid, and esterifies it to produce methyl methacrylate. This route has a long process flow, complex equipment, high investment, expensive raw material high-purity isobutylene, low overall selectivity, and high production costs.
[0007] Ethylene carbonylation process: Ethylene is carbonylated with CO and H2 to synthesize propionaldehyde, propionaldehyde is condensed with formaldehyde to generate methacrolein, oxidized to obtain methacrylic acid, and esterified to generate methyl methacrylate. Ethylene can also be carbonylated with CO and methanol in one step to prepare methyl propionate, which can be condensed with formaldehyde to directly generate methyl methacrylate.
[0008] Propylene carbonylation method is to produce isobutyraldehyde through propylene carbonylation, and then produce MAA through dehydrogenation and oxidation of isobutyraldehyde, or first oxidize to produce isobutyric acid and then dehydrogenate to produce MAA. Rohm companies in France and Germany have completed industrial development.
[0009] In this application, MAA is prepared by hydrolysis-dehydrogenation-condensation with methyl propionate and water as raw materials. There is no MAA preparation technology using this as raw material in the literature. Only similar processes are reported: Wolfgang et al. catalyzed the reaction of propionic acid and formaldehyde with K / Al2O3 / SiO2 catalyst, and the conversion rate was only 33% and the selectivity was 49%. In 1988, Mamoru Ai reported that PV catalyst was used for the condensation reaction of propionic acid and formaldehyde. The study found that when the molar ratio of propionic acid to formaldehyde was 2, the yield of methacrylic acid could reach 39 mol%. Using V-Si-P catalyst, the yield of methacrylic acid under optimized reaction conditions could reach 53 mol% and the selectivity was 82%. In 2003, Mamoru Ai reported that the yield of methacrylic acid on Sn-Si-P catalyst could reach 58%.
[0010] In summary, in the reaction of preparing methacrylic acid by the reaction of methyl propionate with H2O, the design and synthesis of a hydrolysis-dehydrogenation-condensation trifunctional catalyst is key. The catalytic activity of the catalysts reported so far is generally low. Therefore, the development of a novel and highly active catalyst is key and of great significance.
[0011] The reaction process is:
[0012] Summary of the invention
[0013] The problem to be solved by the present invention is to provide a catalytic synthesis method for methacrylic acid, starting from cheap, easily available and stable methyl propionate and water, and preparing methacrylic acid through a suitable catalytic system.
[0014] The technical solution is:
[0015] In a fixed bed reactor, methyl propionate and water in a certain proportion, after being gasified and diluted with an inert gas or without dilution, react on a certain amount of catalyst with the three functions of hydrolysis-anaerobic dehydrogenation-condensation under certain temperature and pressure conditions to produce methacrylic acid and simultaneously produce hydrogen.
[0016] The molar ratio of methyl propionate to water is: 1:(1-9);
[0017] The inert atmosphere includes: N2, Ar, He;
[0018] The inert gas accounts for 5-95% of the total volume of the total gas;
[0019] The mass space velocity of methyl propionate on the catalyst is: 0.3-5h -1 ;
[0020] Reaction temperature: 300-650℃;
[0021] Reaction pressure: 0.5-25atm.
[0022] Provide a solution:
[0023] The molar ratio of methyl propionate to water is: 1:(1-7);
[0024] The inert gas accounts for 15-85% of the total volume of the total gas;
[0025] The mass space velocity of methyl propionate on the catalyst is: 0.3-4h -1 ;
[0026] Reaction temperature: 350-600℃;
[0027] Reaction pressure: 0.5-15atm.
[0028] Provide a solution:
[0029] The molar ratio of methyl propionate to water is: 1:(1-5);
[0030] The inert gas accounts for 25-75% of the total volume of the total gas;
[0031] The mass space velocity of methyl propionate on the catalyst is: 0.3-3h -1 ;
[0032] Reaction temperature: 400-550°C;
[0033] Reaction pressure: 5-15atm.
[0034] The catalyst having the three functions of hydrolysis-oxygen-free dehydrogenation-condensation has the following structural characteristics:
[0035] The first-stage component has the function of catalyzing the hydrolysis of methyl propionate; the second-stage component has the function of catalyzing the anaerobic dehydrogenation of methanol; and the third-stage component has the function of catalyzing the condensation of formaldehyde and propionic acid.
[0036] The specific properties and composition of the catalyst having the three functions of hydrolysis-oxygen-free dehydrogenation-condensation are as follows:
[0037] The first-stage component is an active component with weak to medium acidity, selected from: natural weak or medium acid clay, including kaolin, bentonite, montmorillonite, talc, natural zeolite; metal oxides, including Al2O3, Ga2O3, Cr2O3, HfO2, ZrO2, TiO2, SnO2, GeO2, Sb2O5, SiO2, MoO3; weak acid synthetic molecular sieves, including HX, HY, Hβ, SAPO-34, SAPO-11; metal phosphates (including AlPO4, FePO4, Ti3(PO4)4, Zr3(PO4)4, BiPO4, Zn3(PO4)2), and mixtures of the above-mentioned weak and medium acid catalysts;
[0038] The second-stage component is an active component having an oxygen-free dehydrogenation function, selected from: ZnO, MgO, CuO, Ag, Au, Pt, Pd, Rh, CuZn, RuZn alloy and mixtures thereof;
[0039] The third-level component is an active component with medium to strong acidity (or alkalinity or both acidity and alkalinity), selected from: WO3, Nb2O5, Ta2O5, B2O3; Cs2O, Rb2O, SrO, CaO, BaO, La2O3, Ba(OH)2; heteropolyacids, including phosphotungstic acid, phosphomolybdic acid, silicotungstic acid; SO4 2- / TiO2、SO4 2- / ZrO2、SO4 2- / Fe2O3 and their mixtures.
[0040] In the catalyst with the three functions of hydrolysis-dehydrogenation-condensation, the second-stage component accounts for 10-25wt% of the total mass of the catalyst, the third-stage component accounts for 5-10wt% of the total mass of the catalyst, and the rest is the first-stage component.
[0041] The preparation method of the catalyst with the three functions of hydrolysis-oxygen-free dehydrogenation-condensation is as follows: firstly prepare a colloidal solution of a second-stage component, then adsorb a third-stage component onto the colloid of the second component, and finally load the colloid adsorbed with the third-stage component onto the first-stage component by electrostatic adsorption or impregnation, and finally calcine, the calcination temperature is 500-800°C, the calcination time is 4-24h, and the calcination atmosphere is air, or an oxygen-containing (5-99.9%) inert atmosphere, or a hydrogen-containing (5-50%) inert atmosphere.
[0042] The process is carried out in a fixed bed reactor. On a multifunctional catalyst, methyl propionate is first hydrolyzed with water to produce equimolar propionic acid and methanol. At the same time, the methanol generated in situ is oxygen-free dehydrogenated on the above catalyst to produce formaldehyde, and then the formaldehyde and propionic acid are condensed to produce methacrylic acid, while hydrogen is co-produced.
[0043] The process of methanol anaerobic dehydrogenation to produce anhydrous formaldehyde is the key. This is conducive to reducing the influence of water on the condensation process of propionic acid and formaldehyde. At the same time, the consumption of formaldehyde can promote the balance of methanol anaerobic dehydrogenation reaction to move to the right, and the reactions promote each other.
[0044] Beneficial technical effects
[0045] 1. The catalyst raw materials used in the present invention are cheap and readily available, the preparation process is controllable and easy to operate, and the effective occurrence of the reaction of preparing methacrylic acid from methyl propionate and water as raw materials can be achieved;
[0046] 2. The catalyst has good stability and hydrothermal stability, and the reaction process is simple, controllable and easy to operate. The yield of methacrylic acid can reach up to 73%, and hydrogen can also be co-produced. DETAILED DESCRIPTION
[0047] In order to further explain the present invention in detail, several specific implementation cases are given below, but the present invention is not limited to these embodiments.
[0048] Example 1
[0049] The second-stage component nano ZnO powder with a particle size of 20-50nm is dispersed in 100mL of water (wherein the solid component content is 30wt%), and stirred to disperse into a colloidal suspension, and then the third-stage component precursor ammonium niobium oxalate is added, and after stirring for sufficient adsorption, the first-stage component alumina is added to the second-stage component colloidal solution adsorbed with the third-stage component precursor; the amount of the above components added is calculated according to the mass ratio of the corresponding active components, the first-stage component Al2O3: the second-stage component ZnO: the third-stage component Nb2O5 = 75:25:10; after stirring for sufficient adsorption, the mixture is filtered, washed thoroughly, dried, and calcined at 500°C in N2 containing 5v / v% oxygen for 6h (the oxygen content percentage is volume percentage, the same as in the following embodiments).
[0050] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:1 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 1h -1 The reaction was carried out at 500°C and 3 atm and monitored online by gas chromatography. The product yield and selectivity after 8 h of reaction are shown in Table 1.
[0051] Example 2 (using the catalyst sample in Example 1)
[0052] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added to a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:5 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 1h -1 The reaction was carried out at 500°C and 3 atm and monitored online by gas chromatography. The product yield and selectivity after 8 h of reaction are shown in Table 1.
[0053] Example 3 (using the catalyst sample in Example 1)
[0054] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:7 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 1h -1 The reaction was carried out at 500°C and 3 atm and monitored online by gas chromatography. The product yield and selectivity after 8 h of reaction are shown in Table 1.
[0055] Example 4 (using the catalyst sample in Example 1)
[0056] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added to a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:9 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 1h -1 The reaction was carried out at 500°C and 3 atm and monitored online by gas chromatography. The product yield and selectivity after 8 h of reaction are shown in Table 1.
[0057] Example 5
[0058] Disperse the second-stage component nano CuO powder with a particle size of 30-50nm in 100mL of water (wherein the solid component content is 60wt%), stir and disperse into a colloidal suspension, then add the third-stage component precursors ammonium tungstate and ammonium niobium oxalate (calculated at a mass ratio of WO3:Nb2O5 of 1 / 5), stir and fully adsorb, and then add the first-stage component AlPO4 to the second-stage component colloidal solution adsorbed with the third-stage component precursor; the amount of the above components added is calculated according to the mass ratio of the corresponding active components, the first-stage component AlPO4: the second-stage component CuO: the third-stage component WO3-Nb2O5=85:10:5; after stirring and fully adsorbing, filter, wash thoroughly, dry, and roast at 600℃ in 5% oxygen N2 for 4h.
[0059] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added to a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:4 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 5% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 1h -1 The reaction was carried out at 550°C and 3 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0060] Example 6 (using the catalyst sample in Example 5)
[0061] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:4 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 15% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 1h -1 The reaction was carried out at 550°C and 3 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0062] Example 7 (using the catalyst sample in Example 5)
[0063] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:4 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 25% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 1h -1 The reaction was carried out at 550°C and 3 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0064] Example 8 (using the catalyst sample in Example 5)
[0065] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:4 were gasified and then introduced into the reactor with inert gas. The inert dilution atmosphere was N2, and the volume of inert gas accounted for 75% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 1h -1 The reaction was carried out at 550°C and 3 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0066] Example 9 (using the catalyst sample in Example 5)
[0067] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:4 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 85% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 1h -1 The reaction was carried out at 550°C and 3 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0068] Example 10 (using the catalyst sample in Example 5)
[0069] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added to a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:4 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 95% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 1h -1 The reaction was carried out at 550°C and 3 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0070] Embodiment 11
[0071] Nano CuO powder and nano MgO powder with particle sizes of 20-40nm and 40-60nm of the second-level component (calculated at a CuO:MgO mass ratio of 1 / 1) are dispersed in 100mL of water (wherein the solid component content is 80wt%), stirred and dispersed into a colloidal suspension, and then the third-level component phosphotungstic acid is added. After stirring for sufficient adsorption, the first-level component Zr3(PO4)4 is added to the above-mentioned colloidal solution of the second-level component adsorbed with the third-level component; the amount of the above-mentioned components added is calculated according to the mass ratio of the corresponding active components, the first-level component Zr3(PO4)4: the second-level component CuO-MgO: the third-level component phosphotungstic acid = 75:25:10; after stirring for sufficient adsorption, the mixture is filtered, washed thoroughly, dried, and calcined at 800℃ in Ar containing 10% oxygen for 6h.
[0072] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was Ar, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 0.3 h -1 The reaction was carried out at 550°C and 1 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0073] Example 12 (using the catalyst sample in Example 11)
[0074] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were vaporized and then introduced into the reactor with an inert gas. The inert dilution atmosphere was Ar, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 1h -1 The reaction was carried out at 550°C and 1 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0075] Example 13 (using the catalyst sample in Example 11)
[0076] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was Ar, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 3h -1 The reaction was carried out at 550°C and 1 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0077] Example 14 (using the catalyst sample in Example 11)
[0078] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added to a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was Ar, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 4h -1 The reaction was carried out at 550°C and 1 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0079] Example 15 (using the catalyst sample in Example 11)
[0080] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added to a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was Ar, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 5h -1 The reaction was carried out at 550°C and 1 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0081] Example 16
[0082] The second-stage component 20-100nm nanosheet Ag is dispersed in 100mL of ethanol (wherein the solid component content is 20wt%), stirred and dispersed into a colloidal suspension, and then the third-stage component precursor strontium nitrate is added. After stirring for sufficient adsorption, the mixed oxide of the first-stage component SnO2-Al2O3 (calculated at a mass ratio of 1 / 1) is added to the above-mentioned second-stage component colloidal solution adsorbed with the third-stage component precursor; the amount of the above-mentioned components added is calculated according to the mass ratio of the corresponding active components, the first-stage component SnO2-Al2O3: the second-stage component Ag: the third-stage component SrO=85:10:5; after stirring for sufficient adsorption, filter, wash thoroughly, dry, and roast at 500℃ in N2 containing 99.9% oxygen for 6h.
[0083] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 0.5 h -1 The reaction was carried out at 300°C and 5 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0084] Example 17 (using the catalyst sample in Example 16)
[0085] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 0.5 h -1 The reaction was carried out at 350°C and 5 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0086] Example 18 (using the catalyst sample in Example 16)
[0087] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 0.5 h -1 The reaction was carried out at 400°C and 5 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0088] Example 19 (using the catalyst sample in Example 16)
[0089] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 0.5h -1 The reaction was carried out at 550°C and 5 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0090] Example 20 (using the catalyst sample in Example 16)
[0091] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 0.5 h -1 The reaction was carried out at 650°C and 5 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0092] Embodiment 21
[0093] Preparation of the second-stage component CuZn alloy colloid
[0094] Copper nitrate trihydrate and zinc nitrate hexahydrate were dissolved in 100 mL of anhydrous ethanol (with a solid content of 40 wt%) in a molar ratio of 1:1. Glycerol was added according to its reaction with metal ions (Cu 2+ and Zn 2+ ) in a total molar ratio of 6:1, added to the above solution and stirred evenly. Ammonium carbonate was dissolved in 100mL of deionized water (the molar ratio of ammonium carbonate to the total amount of metal ions was 10:1), and then added to the above metal ion solution at a rate of 10mL / min. The resulting precipitate was a mixed colloidal solution of copper hydroxide and zinc hydroxide. Electron microscopy characterization showed that the size of the mixed nanoparticles was about 40-70nm.
[0095] In the above-mentioned second-stage component colloidal solution, add the third-stage component precursor strontium nitrate and barium nitrate (calculated at a mass ratio of SrO and BaO of 1 / 1), stir for sufficient adsorption, and then add the first-stage component HfO2 to the above-mentioned second-stage component colloidal solution adsorbed with the third-stage component precursor; the amount of the above-mentioned components added is calculated according to the mass ratio of the corresponding active components, first-stage component HfO2: second-stage component CuZn alloy: third-stage component SrO-BaO=75:25:10; after stirring for sufficient adsorption, filter, wash thoroughly, dry, and roast at 500℃ in Ar containing 5% H2 for 6h.
[0096] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 0.5 h -1 The reaction was carried out under the conditions of 550°C and 0.5 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0097] Example 22 (using the catalyst sample in Example 21)
[0098] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 0.5 h -1 The reaction was carried out at 550°C and 5 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0099] Example 23 (using the catalyst sample in Example 21)
[0100] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 0.5 h -1 The reaction was carried out under the conditions of 550°C and 10 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0101] Example 24 (using the catalyst sample in Example 21)
[0102] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 0.5 h -1 The reaction was carried out under the conditions of 550°C and 15 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0103] Example 25 (using the catalyst sample in Example 21)
[0104] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 0.5 h -1 The reaction was carried out under the conditions of 550°C and 25 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0105] Embodiment 26
[0106] Disperse the second-stage component nano-MgO with a particle size of 40-60nm in 100mL of water (wherein the solid component content is 40wt%), stir and disperse into a colloidal suspension, then add the third-stage component precursor ammonium tungstate, stir and fully adsorb, and then add the first-stage component ZrO2 to the second-stage component colloidal solution adsorbed with the third-stage component precursor; the amount of the above components added is calculated according to the mass ratio of the corresponding active components, the first-stage component ZrO2: the second-stage component MgO: the third-stage component WO3 = 75:25:10; after stirring and fully adsorbing, filter, wash, dry, and air-roast at 700℃ for 24h.
[0107] The obtained sample was pressed into tablets with a size of 20-60 mesh, and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:5 were gasified and then introduced into the reactor with inert gas. The inert dilution atmosphere was He, and the volume of inert gas accounted for 20% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 0.3h -1 The reaction was carried out at 400°C and 2 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0108] Embodiment 27
[0109] Preparation of the Secondary Component AgZn Alloy Colloid
[0110] Silver nitrate and zinc nitrate hexahydrate were dissolved in 100 mL of deionized water (with a solid content of 40 wt%) in a molar ratio of 3:1. Glycerol was added according to its reaction with metal ions (Ag + and Zn 2+ ) total molar ratio of 10:1, add to the above solution, and stir evenly. Dissolve ammonium carbonate in 100mL deionized water (the molar ratio of ammonium carbonate to the total amount of metal ions is 8:1), and then add it to the above metal ion solution at a rate of 10mL / min. The resulting precipitate is a mixed colloidal solution of silver hydroxide and zinc hydroxide. Electron microscopy characterization shows that the size of the mixed nanoparticles is about 40-60nm.
[0111] Add the third-stage component precursor ammonium borate to the above-mentioned second-stage component colloidal solution, stir for sufficient adsorption, and then add the first-stage component TiO2 to the above-mentioned second-stage component colloidal solution that has adsorbed the third-stage component precursor; the amount of the above-mentioned components added is calculated according to the mass ratio of the corresponding active components, first-stage component TiO2: second-stage component AgZn alloy: third-stage component B2O3 = 85:10:5; after stirring for sufficient adsorption, filter, wash thoroughly, dry, and roast at 500°C in N2 containing 10H2 for 12 hours.
[0112] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 0.3h -1 The reaction was carried out at 500°C and 5 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0113] Embodiment 28
[0114] In the second-stage component colloidal solution of the above-mentioned Example 27, sodium tantalate, a precursor of the third-stage component, is added, and after stirring for sufficient adsorption, SnO2, the first-stage component, is added to the second-stage component colloidal solution adsorbing the third-stage component precursor; the amounts of the above-mentioned components added are calculated according to the mass ratios of the corresponding active components, first-stage component SnO2: second-stage component AgZn alloy: third-stage component Ta2O5=85:10:5; after stirring for sufficient adsorption, the solution is filtered, washed thoroughly, dried, and calcined at 500°C in N2 containing 50% H2 for 6 hours.
[0115] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 0.3h -1 The reaction was carried out at 500°C and 5 atm and monitored online by gas chromatography. The product yield and selectivity after 36 h of reaction are shown in Table 1.
[0116] Embodiment 29
[0117] In the second-stage component colloidal solution of the above-mentioned Example 27, the third-stage component precursor calcium nitrate is added, and after stirring for sufficient adsorption, the first-stage component MoO3 is added to the above-mentioned second-stage component colloidal solution that has adsorbed the third-stage component precursor; the amount of the above-mentioned components added is calculated according to the mass ratio of the corresponding active components, first-stage component MoO3: second-stage component AgZn alloy: third-stage component CaO = 85:10:5; after stirring for sufficient adsorption, filter, wash thoroughly, dry, and roast at 500°C in N2 containing 30% H2 for 6 hours.
[0118] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 0.3h -1 The reaction was carried out at 500°C and 5 atm and monitored online by gas chromatography. The product yield and selectivity after 60 h of reaction are shown in Table 1.
[0119] Embodiment 30
[0120] In the second-stage component colloidal solution of the above-mentioned embodiment 21, cesium carbonate, a precursor of the third-stage component, is added. After stirring for sufficient adsorption, the first-stage component GeO2 is added to the second-stage component colloidal solution adsorbing the third-stage component precursor. The amounts of the above-mentioned components added are calculated according to the mass ratios of the corresponding active components, first-stage component GeO2: second-stage component CuZn alloy: third-stage component Cs2O=75:25:10. After stirring for sufficient adsorption, the mixture is filtered, washed thoroughly, dried, and calcined at 600°C in Ar containing 5% H2 for 6 hours.
[0121] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 0.3h -1 The reaction was carried out at 500°C and 5 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0122] Embodiment 31
[0123] Preparation of RuZn alloy colloid as the second component
[0124] Ruthenium trichloride and zinc nitrate hexahydrate were dissolved in 100 mL of deionized water (with a solid content of 10 wt%) in a molar ratio of 1:3. Glycerol was added according to its reaction with metal ions (Ru 3+ and Zn 2+) in a total molar ratio of 10:1, added to the above solution and stirred evenly. Ammonium bicarbonate was dissolved in 100mL of deionized water (the molar ratio of ammonium bicarbonate to the total amount of metal ions was 8:1), and then added to the above metal ion solution at a rate of 10mL / min. The resulting precipitate was a mixed colloidal solution of ruthenium hydroxide and zinc hydroxide. Electron microscopy characterization showed that the size of the mixed nanoparticles was about 50-60nm.
[0125] Add the third-stage component precursor rubidium nitrate to the above-mentioned second-stage component colloidal solution, stir for sufficient adsorption, and then add the first-stage component Sb2O5 to the above-mentioned second-stage component colloidal solution that has adsorbed the third-stage component precursor; the amount of the above-mentioned components added is calculated according to the mass ratio of the corresponding active components, first-stage component Sb2O5: second-stage component RuZn alloy: third-stage component Rb2O=85:10:5; after stirring for sufficient adsorption, filter, wash thoroughly, dry, and roast at 500℃ in N2 containing 30% H2 for 6h.
[0126] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 0.3h -1 The reaction was carried out at 500°C and 5 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0127] Embodiment 32
[0128] In the second-stage component colloidal solution of the above-mentioned Example 31, the third-stage component precursor barium nitrate is added, and after stirring for sufficient adsorption, the first-stage component Ga2O3 is added to the above-mentioned second-stage component colloidal solution that has adsorbed the third-stage component precursor; the amounts of the above-mentioned components added are calculated according to the mass ratios of the corresponding active components, first-stage component Ga2O3: second-stage component RuZn alloy: third-stage component BaO=85:10:5; after stirring for sufficient adsorption, the mixture is filtered, washed thoroughly, dried, and calcined at 500°C in N2 containing 30% H2 for 6 hours.
[0129] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 0.3h -1 The reaction was carried out at 500°C and 5 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0130] Embodiment 33
[0131] In the second-stage component colloidal solution of the above-mentioned Example 31, the third-stage component barium hydroxide is added, and after stirring for sufficient adsorption, the first-stage component calcium zeolite is added to the above-mentioned second-stage component colloidal solution that has adsorbed the third-stage component; the amounts of the above-mentioned components added are calculated according to the mass ratios of the corresponding active components, first-stage component calcium zeolite: second-stage component RuZn alloy: third-stage component Ba(OH)2=85:10:5; after stirring for sufficient adsorption, the mixture is filtered, washed thoroughly, dried, and calcined at 600°C in N2 containing 30% H2 for 6 hours.
[0132] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 0.3h -1 The reaction was carried out at 500°C and 5 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0133] Embodiment 34
[0134] Preparation of the Secondary Component Nano-Au Colloid
[0135] In a mixed solution of 50mL formalin solution and 50mL cyclohexane, add 0.067mol n-hexylamine, stir at room temperature for 30min, separate the upper cyclohexane phase, add it to 50mL chloroauric acid aqueous solution (wherein the molar number of Au is 0.5mmol), stir at room temperature for 30min. Separate the upper cyclohexane phase to obtain a nano-gold colloidal solution. Electron microscopy characterization shows that the size of the gold nanoparticles is 10-20nm.
[0136] Add lanthanum nitrate, a precursor of the third-level component, to the above-mentioned colloidal solution of the second-level component, and after stirring for sufficient adsorption, add kaolin, the first-level component, to the above-mentioned colloidal solution of the second-level component that has adsorbed the precursor of the third-level component; the amount of the above-mentioned components added is calculated according to the mass ratio of the corresponding active components, first-level component kaolin: second-level component Au: third-level component La2O3=85:10:5; after stirring for sufficient adsorption, filter, wash thoroughly, dry, and roast at 500℃ in N2 containing 30% H2 for 6h.
[0137] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 0.3h -1The reaction was carried out at 500°C and 5 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0138] Embodiment 35
[0139] In the second-stage component colloidal solution of the above-mentioned embodiment 34, the third-stage component phosphomolybdic acid is added, and after stirring for sufficient adsorption, the first-stage component HY is added to the above-mentioned second-stage component colloidal solution adsorbed with the third-stage component; the amount of the above-mentioned components added is calculated according to the mass ratio of the corresponding active components, first-stage component HY: second-stage component Au: third-stage component phosphomolybdic acid = 85:10:5; after stirring for sufficient adsorption, the mixture is filtered, washed thoroughly, dried, and calcined at 600°C in N2 containing 30% H2 for 6 hours.
[0140] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 0.3h -1 The reaction was carried out at 500°C and 5 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0141] Embodiment 36
[0142] To the second-stage component colloidal solution of the above-mentioned embodiment 34, add the third-stage component phosphotungstic acid, and after stirring for sufficient adsorption, add the first-stage component SAPO-34 to the above-mentioned second-stage component colloidal solution adsorbed with the third-stage component; the amounts of the above-mentioned components added are calculated according to the mass ratios of the corresponding active components, first-stage component SAPO-34: second-stage component Au: third-stage component phosphotungstic acid = 85:10:5; after stirring for sufficient adsorption, filter, wash thoroughly, dry, and roast at 500°C in N2 containing 30% H2 for 6 hours.
[0143] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 0.3h -1 The reaction was carried out at 500°C and 5 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0144] Embodiment 37
[0145] Preparation of Nano-AuPt Alloy Colloid
[0146] In a mixed solution of 50mL formalin solution and 50mL cyclohexane, add 0.067mol n-hexylamine, stir at room temperature for 30min, separate the upper cyclohexane phase, add it to a mixed aqueous solution of 50mL chloroauric acid and chloroplatinic acid (where the molar numbers of Au and Pt are 0.25 and 0.25mmol respectively), and stir at 40℃ for 30min. Separate the upper cyclohexane phase to obtain a nano AuPt colloidal solution. Electron microscopy characterization shows that the size of AuPt alloy nanoparticles is 10-15nm.
[0147] In the above second-stage component colloidal solution, add 10wt% SO4 of the third-stage component 2- / Fe2O3, after sufficient adsorption by stirring, the first-stage component Ti3(PO4)4 is added to the colloidal solution of the second-stage component adsorbed with the third-stage component; the amount of the above-mentioned components added is calculated according to the mass ratio of the corresponding active components, the first-stage component Ti3(PO4)4: the second-stage component AuPt alloy: the third-stage component 10wt% SO4 2- / Fe2O3=85:10:5;After stirring for sufficient adsorption, filter, wash thoroughly, dry, and roast at 500℃ in N2 containing 30% H2 for 6h.
[0148] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 0.3h -1 The reaction was carried out at 500°C and 5 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0149] Embodiment 38
[0150] Preparation of Nano-AuPd Alloy Colloid
[0151] In a mixed solution of 50mL formalin solution and 50mL cyclohexane, add 0.067mol n-decylamine, stir at room temperature for 30min, separate the upper cyclohexane phase, add it to a mixed aqueous solution of 50mL chloroauric acid and chloropalladic acid (where the molar numbers of Au and Pd are 0.1 and 0.4mmol respectively), and stir at 60℃ for 30min. Separate the upper cyclohexane phase to obtain a nano AuPd colloidal solution. Electron microscopy characterization shows that the size of AuPd alloy nanoparticles is 15-20nm.
[0152] In the above second-stage component colloidal solution, add 30wt% SO4 of the third-stage component 2- / TiO2, after sufficient adsorption by stirring, the first-stage component Zn3(PO4)2 is added to the colloidal solution of the second-stage component adsorbed with the third-stage component; the amount of the above-mentioned components added is calculated according to the mass ratio of the corresponding active components, the first-stage component Zn3(PO4)2: the second-stage component AuPd alloy: the third-stage component 30wt% SO4 2- / TiO2=85:10:5;After stirring for sufficient adsorption, filter, wash thoroughly, dry, and roast at 500℃ in N2 containing 30% H2 for 6h.
[0153] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 0.3h -1 The reaction was carried out at 500°C and 5 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0154] Embodiment 39
[0155] Preparation of Nano-AuRh Alloy Colloid
[0156] In a mixed solution of 50 mL formalin solution and 50 mL cyclohexane, add 0.067 mol n-decylamine, stir at room temperature for 30 min, separate the upper cyclohexane phase, add it to a mixed aqueous solution of 50 mL chloroauric acid and rhodium trichloride (where the molar numbers of Au and Rh are 0.4 and 0.1 mmol, respectively), and stir at 80 ° C for 30 min. The upper cyclohexane phase is separated to obtain a nano AuRh colloidal solution. Electron microscopy characterization shows that the size of AuRh alloy nanoparticles is 10-20 nm.
[0157] In the above second-stage component colloidal solution, add 50wt% SO4 of the third-stage component 2- / ZrO2, after sufficient adsorption by stirring, the first-stage component BiPO4 is added to the colloidal solution of the second-stage component adsorbed with the third-stage component; the amount of the above-mentioned components added is calculated according to the mass ratio of the corresponding active components, the first-stage component BiPO4: the second-stage component AuRh alloy: the third-stage component 50wt% SO4 2- / ZrO2=85:10:5;After stirring for sufficient adsorption, filter, wash thoroughly, dry, and roast at 500℃ in N2 containing 30% H2 for 6h.
[0158] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 0.3h -1 The reaction was carried out at 500°C and 5 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0159] Comparative Example 1
[0160] Add the mixture of BaO and Ga2O3 directly into the RuZn alloy colloidal solution of the above-mentioned Example 31, and add the materials according to the first-level component Ga2O3: the second-level component RuZn alloy: the third-level component BaO = 85:10:5; after sufficient stirring, dry, and roast at 500°C in N2 containing 30% H2 for 6 hours.
[0161] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 0.3h -1 The reaction was carried out at 500°C and 5 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0162] Comparative Example 2
[0163] Dissolve barium nitrate in 100 mL of water (with a solid component content of 30 wt%), then add Ga2O3 to the aqueous solution, and add the first-stage component Ga2O3: the third-stage component BaO = 5:85; after stirring for sufficient adsorption, filter, wash thoroughly, dry, and roast at 500°C in N2 containing 30% H2 for 6 hours.
[0164] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 0.3h -1 The reaction was carried out at 500°C and 5 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0165] Comparative Example 3
[0166] In the second-stage component colloidal solution of the above-mentioned Example 31, the first-stage component Ga2O3 is added; the amount of the above-mentioned components added is calculated according to the mass ratio of the corresponding active components, the first-stage component Ga2O3: the second-stage component RuZn alloy = 85:10; after stirring for sufficient adsorption, it is filtered, washed thoroughly, dried, and calcined at 500°C in N2 containing 30% H2 for 6 hours.
[0167] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 0.3h -1 The reaction was carried out at 500°C and 5 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0168] Comparative Example 4
[0169] Add the mixture of barium nitrate and Ga2O3 directly into the RuZn alloy colloidal solution of the above-mentioned Example 31, and add the materials according to the first-level component Ga2O3: the second-level component RuZn alloy: the third-level component BaO = 85:10:5; after stirring for sufficient adsorption, filter, wash thoroughly, dry, and roast at 500℃ in N2 containing 30% H2 for 6h.
[0170] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 0.3h -1 The reaction was carried out at 500°C and 5 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0171] Comparative Example 5
[0172] Dissolve 5 g of cerium nitrate hexahydrate in 100 mL of deionized water, take 50 mL of 28% ammonia water and add it into 50 mL of water. Add the ammonia solution into the fully stirred cerium nitrate aqueous solution at a rate of 10 mL / min. Electron microscopy characterization of the obtained colloidal solution shows that the size of the cerium oxide nanoparticles is about 40-50 nm.
[0173] Lanthanum nitrate is added to the above-mentioned cerium oxide (second-stage component) colloidal solution according to (La2O3:CeO2=1:3 mass ratio), and after stirring for sufficient adsorption, the first-stage component, micron-grade kaolin, is added to adsorb the above-mentioned cerium oxide colloid. The mass of the first-stage component added is (La2O3:CeO2:kaolin=1:3:6 mass ratio). After stirring for sufficient adsorption, it is filtered, washed thoroughly, dried, and air-roasted at 500°C for 4 hours.
[0174] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 0.3h -1 The reaction was carried out at 500°C and 5 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0175] Comparative Example 6
[0176] 5 g of ferric nitrate nonahydrate was dissolved in 100 mL of deionized water, 7.3 g of ammonium molybdate was dissolved in 50 mL of deionized water, and 50 mL of ethylene glycol was added. The ammonium molybdate solution was added to the fully stirred ferric nitrate aqueous solution at a rate of 10 mL / min to obtain a mixed colloidal solution. Electron microscopy showed that the size of the iron molybdate nanoparticles was approximately 40-70 nm.
[0177] To the above iron molybdate (second-stage component) colloidal solution, phosphomolybdic acid is added according to (phosphotungstic acid: iron molybdate = 1:5 mass ratio), stirred for sufficient adsorption, and then the first-stage component, micron-grade SAPO-34 (1-1000 microns) is added to adsorb the above iron molybdate colloid. The mass of the first-stage component added is (phosphomolybdic acid: iron molybdate: HY = 1:5:35 mass ratio). After stirring for sufficient adsorption, it is filtered, washed thoroughly, dried, and air-roasted at 500°C for 4 hours.
[0178] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 0.3h -1 The reaction was carried out at 500°C and 5 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0179] Comparative Example 7
[0180] Dissolve 5 g of cobalt nitrate in 100 mL of deionized water, take 50 mL of 28% ammonia water and add it to 50 mL of glycerol, add the ammonia solution into the fully stirred cobalt nitrate aqueous solution at a rate of 10 mL / min, and the obtained mixed colloidal solution is characterized by electron microscopy, which shows that the size of the cobalt oxide nanoparticles is about 30-50 nm.
[0181] In the above cobalt oxide (secondary component) colloidal solution, (SO4 2- / ZrO2:Co3O4=1:15 mass ratio) add 40wt% SO4 2- / ZrO2, after stirring for sufficient adsorption, add the first-stage component micron-sized Zn3(PO4)2 (1-1000 microns) to adsorb the above cobalt oxide colloid, the mass of the added first-stage component is according to (third-stage component: second-stage component: first-stage component = 1:15:84 mass ratio), after stirring for sufficient adsorption, filter, wash thoroughly, dry, and calcine at 500°C in air atmosphere for 4 hours.
[0182] The obtained sample was pressed into tablets with a mesh size of 20-60 and then added into a fixed bed reactor. Methyl propionate and water in a molar ratio of 1:3 were gasified and then introduced into the reactor with an inert gas. The inert dilution atmosphere was N2, and the volume of the inert gas accounted for 60% of the total gas volume. The mass space velocity of methyl propionate on the catalyst was 0.3h -1 The reaction was carried out at 500°C and 5 atm and monitored online by gas chromatography. The product yield and selectivity after 6 h of reaction are shown in Table 1.
[0183] Table 1 Reaction evaluation results
[0184]
[0185]
[0186] From Examples 1-4, it can be seen that the higher the water content, the higher the methyl propionate conversion rate, but the selectivity decreases, the methanol conversion rate decreases, the hydrogen selectivity increases, and the appropriate range of water content is 1 to 5. From Examples 5-10, it can be seen that the higher the proportion of inert gas, the higher the conversion rate, and the selectivity is slightly improved. The appropriate range of inert gas proportion is 25 to 75%. From Examples 11-15, it can be seen that the higher the mass space velocity, the lower the conversion rate, and the lower the selectivity. The appropriate range of mass space velocity is 0.3 to 3h -1. From Examples 16-20, it can be seen that the higher the reaction temperature, the higher the conversion rate, the lower the methacrylic acid selectivity, but the hydrogen selectivity is improved, and the suitable range of reaction temperature is 400-550°C. From Examples 21-25, it can be seen that the higher the reaction pressure, the lower the conversion rate, the lower the selectivity, and the suitable range of reaction pressure is 1-5atm. From Comparative Example 1 and Example 32, it can be seen that the mechanical mixing of the three-stage active components, although methyl propionate and methanol are partially converted, the selectivity is very low. From Comparative Examples 2, 3 and Example 32, it can be seen that one of the second and third stage components is missing, although methyl propionate is partially converted, the selectivity is very low; the lack of the third stage component has little effect on methanol conversion and H2 selectivity. From Comparative Example 4 and Example 32, it can be seen that the catalyst prepared by co-precipitation of the second and third stage components, although methyl propionate and methanol are partially converted, the selectivity is poor. It can be seen from Comparative Examples 5-7 that if the second-stage component does not have a dehydrogenation function, such as an oxide with an oxidation function, under the reaction conditions protected by the patent, although methyl propionate will undergo a hydrolysis reaction, the hydrolysis product methanol cannot be effectively dehydrogenated, and the hydrogen yield and methacrylic acid yield are both low.
Claims
1. A method for preparing methacrylic acid, Features: In a fixed bed reactor, only methyl propionate and water are used as reactants under oxygen-free conditions. After being gasified and diluted with an inert gas, the two reactants react on a trifunctional catalyst with an oxygen-free dehydrogenation function to produce methacrylic acid and co-produce hydrogen. The trifunctional catalyst with oxygen-free dehydrogenation function is composed of three-stage components, wherein the second-stage component is an active component with oxygen-free dehydrogenation function, selected from: one or more of ZnO, MgO, CuO, Ag, Au, Pt, Pd, Rh, CuZn, RuZn alloy and mixtures thereof; The molar ratio of methyl propionate to water is: 1:(1-9); The inert atmosphere includes: N 2 , Ar, He or more; the inert gas accounts for 5-95% of the total volume of the total gas; The mass space velocity of methyl propionate on the catalyst is: 0.3-5 h -1 ; Reaction temperature: 300-650 ℃; Reaction pressure: 0.5-25 atm; The trifunctional catalyst containing oxygen-free dehydrogenation function has the following structural characteristics: The first-stage components are active components that catalyze hydrolysis reactions; the second-stage components are active components that catalyze anaerobic dehydrogenation reactions; and the third-stage components are active components that catalyze condensation reactions; wherein the active components that catalyze anaerobic dehydrogenation reactions are only distributed on the active components that catalyze hydrolysis reactions, and the active components that catalyze condensation reactions are only distributed on the active components that catalyze anaerobic dehydrogenation reactions; The active ingredients for catalyzing the hydrolysis reaction are the following acidic active components: natural acidic clays, including kaolin, montmorillonite, bentonite, natural zeolite, and talc; metal oxides, including silicon oxide, aluminum oxide, zirconium oxide, titanium oxide, molybdenum oxide, gallium oxide, tin oxide, germanium oxide, chromium oxide, antimony oxide, and hafnium oxide; acidic artificial synthetic molecular sieves, including SAPO-34 molecular sieve, HX molecular sieve, SAPO-11 molecular sieve, HY molecular sieve, and Hβ molecular sieve; metal phosphates, including aluminum phosphate, iron phosphate, titanium phosphate, zirconium phosphate, bismuth phosphate, zinc phosphate, and a mixture of the above-mentioned acidic catalysts, one or more of the above-mentioned types; The active components for catalyzing the condensation reaction are the following active components with acidity and alkalinity: lanthanum oxide, niobium oxide, barium oxide, tungsten oxide, barium hydroxide, tantalum oxide, calcium oxide, boron oxide, strontium oxide, rubidium oxide, cesium oxide; heteropoly acids, including H 4 S W 12 O 40 , H 4 PMo 12 O 40 , H 3 PW 12 O 40 ; Solid super acid of sulfate loaded on titanium oxide, solid super acid of sulfate loaded on zirconium oxide, solid super acid of sulfate loaded on iron oxide; and mixtures of one or more of the above components; solid super acid of sulfate loaded on titanium oxide has a sulfate loading of 10-50wt%, solid super acid of sulfate loaded on zirconium oxide has a sulfate loading of 10-50wt%, and solid super acid of sulfate loaded on iron oxide has a sulfate loading of 10-50wt%; The preparation method of the trifunctional catalyst containing the oxygen-free dehydrogenation function is as follows: firstly prepare a colloidal solution of the second-stage component, then adsorb the third-stage component onto the colloid of the second component, and finally load the colloid adsorbed with the third-stage component onto the first-stage component by electrostatic adsorption or impregnation, and finally calcine, the calcination temperature is 500-800°C, and the calcination time is 4-24 hours.
2. The method according to claim 1, Features: The molar ratio of methyl propionate to water is: 1:(1-7); The inert gas accounts for 15-85% of the total volume of the total gas; The mass space velocity of methyl propionate on the catalyst is: 0.3-4 h -1 ; Reaction temperature: 350-600 °C; Reaction pressure: 0.5-15 atm.
3. The method according to claim 1, Features: The molar ratio of methyl propionate to water is: 1:(1-5); The inert gas accounts for 25-75% of the total volume of the total gas; The mass space velocity of methyl propionate on the catalyst is: 0.3-3 h -1 ; Reaction temperature: 400-550 °C; Reaction pressure: 5-15 atm.
4. The method according to claim 1, Features: In the trifunctional catalyst with oxygen-free dehydrogenation function, the second-stage component accounts for 10-25 wt% of the total mass of the catalyst, the third-stage component accounts for 5-10 wt% of the total mass of the catalyst, and the rest is the first-stage component.
5. The method according to claim 1, Features: In the trifunctional catalyst with oxygen-free dehydrogenation function, the second-stage component accounts for 10-20 wt% of the total mass of the catalyst, the third-stage component accounts for 7-10 wt% of the total mass of the catalyst, and the rest is the first-stage component.
6. The method according to claim 1, Features: In the trifunctional catalyst having oxygen-free dehydrogenation function, the second-stage component accounts for 15-20 wt% of the total mass of the catalyst.
7. The method according to claim 1 or 5, Features: The preparation method of the trifunctional catalyst containing the oxygen-free dehydrogenation function is as follows: firstly prepare a colloidal solution of the second-stage component, then adsorb the third-stage component onto the colloid of the second component, and finally load the colloid adsorbed with the third-stage component onto the first-stage component by electrostatic adsorption or impregnation, and finally calcine, the calcination temperature is 600-700°C, and the calcination time is 6-24 hours.
8. The method according to claim 7, Features: In the preparation method of the trifunctional catalyst containing oxygen-free dehydrogenation function, the calcination time is 6-12 h.
Citation Information
Patent Citations
Method for improving reaction yield
CN111689861A
Method for improving reaction yield
US20210283564A1
